2013
DOI: 10.1007/s10529-013-1421-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrophilic amino acids and GC-content on expression of recombinant proteins used in vaccines against foot-and-mouth disease virus in Escherichia coli

Abstract: Epitope-based protein expression in Escherichia coli can be improved by adjusting its amino acid composition and encoding genes. To that end, we analyzed 24 recombinant epitope proteins (rEPs) that carry multiple epitopes derived from VP1 protein of foot-and-mouth disease virus. High level expression of the rEPs was attributed to a high content of Arg, Asn, Asp and Thr, a low content of Gln, Pro and Lys, a high content of hydrophilic amino acids and a higher isoelectric point value resulting from abundant Arg.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…For instance, the probability of expressing the protein in soluble form was inversely correlated to the size of protein [28] , thereby hinting that Seq_len is an essential feature. Besides, the composition of amino acid was found to be a critical factor inducing the metabolic stress during RPP in E. coli [29] ; hence, the expression of recombinant protein can be improved by adjusting the amino acids composition [30] . The present study revealed specifically that the occurrences and occurrence frequencies of amino acids such as Occ_E, Occ_V, OF_E, OF_S, OF_F, OF_M, MNC_A, OF_ MNC_A, and OF_MNC_C are the significant factors for the soluble protein expression in the periplasm of E. coli .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the probability of expressing the protein in soluble form was inversely correlated to the size of protein [28] , thereby hinting that Seq_len is an essential feature. Besides, the composition of amino acid was found to be a critical factor inducing the metabolic stress during RPP in E. coli [29] ; hence, the expression of recombinant protein can be improved by adjusting the amino acids composition [30] . The present study revealed specifically that the occurrences and occurrence frequencies of amino acids such as Occ_E, Occ_V, OF_E, OF_S, OF_F, OF_M, MNC_A, OF_ MNC_A, and OF_MNC_C are the significant factors for the soluble protein expression in the periplasm of E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the occurrences of the hydrophilic residues, i.e., proline (P), tyrosine (Y), histidine (H), glutamine (Q) and asparagine (N) seemed to be key determinants in SVR-Low and RFR-Medium in this study. The protein solubility was proven to be affected by the presence of hydrophilic amino acids in the protein, which may in turn influence the expression levels of recombinant protein in E. coli [30] , [31] . Trevino et al (2007) showed that the solubility of ribonuclease from Streptomyces aureofaciens (RNase Sa) was enhanced by the presence of amino acid residues such as aspartic acid (D), glutamic acid (E) and serine (S) in the protein sequence as compared to the other hydrophilic residues such as asparagine (N), glutamine (Q), and threonine (T) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The eluted solution was loaded into Sephadex G-25 (Sigma), and the solution was finally washed by buffer C (20 mmol/L Tris-HCl, 50 mmol/L NaCl, 0.03% Tween 80, pH 7.6). 22 , 23 …”
Section: Methodsmentioning
confidence: 99%
“…To make sure the purified ferritin is retained in monomer form, pH of buffer C was regulated to 2.0. Then, the denatured protein was evenly divided and dialyzed in buffer D (20 mmol/L Tris-HCl, 0.03% Tween 80, pH 7.6, 50/100/170/300 mmol/L NaCl) at 4 C. 22,23 After dialysis, the protein solutions that contain different NaCl concentrations were placed in 1-cm 2 quartz cuvettes to monitor optical density. Optical density was taken at l ¼ 650 nm.…”
Section: Ferritin Solution Dialysis and Ultraviolet-visible Spectrometry Observationmentioning
confidence: 99%